Possibilities and challenges of social participation in Mental Health (Emancipação, 2025)
The study presents reflections on the challenges and possibilities of social participation in mental health, based on qualitative research that used oral history to explore the life trajectories of twelve individuals, including users and professionals active in the anti-asylum movement. The results highlight the importance of ongoing capacity building and education for professionals, aiming for a practice more committed to citizenship and humanrights values. They indicate that the advances achieved in Brazilian mental health policy, which led to legal milestones and aim to structure a system based on care in freedom and psychosocial attention practices, are closely linked to both formal and informal processes of participation. The research indicates that participation in mental health  requires a distinct, critical, and sensitive approach, capable of recognizing and enhancing strategies that promote users’ autonomy and protagonism.
Keywords: Mental health; Social participation; Psychiatric reform